PENGARUH TERAPI BERMAIN JENGA TERHADAP PENURUNAN KECEMASAN PADA ANAK USIA PRASEKOLAH (4-6 TAHUN) AKIBAT HOSPITALISASI DI MURNI TEGUH MEMORIAL HOSPITAL - Livia Tamara; Muhammad Taufik Daniel Hasibuan (Indonesian Trust Nursing Journal, 2023)
Hospitalization is a process that plans or emergency requires the child to stay in the hospital, to undergo therapy and treatment until his return home. Hospitalization has a psychological impact in several ways, such as depression, stress, fear and experiencing anxiety. One of the recommended interventions is the provision of jenga play therapy. The purpose of this study aims to find out the effect of jenga play therapy on decreasing anxiety in preschool-aged children (4-6 years) due to hospitalization at Murni Teguh Memorial Hospital. This type of research is quasy experimental with the design "One group pre test – Post test". The total sample in the study was 30 preschool-age children using the total sampling technique. Data collection is done before and after play therapy using Spance Children Anxiety Scale (SCAS) instrument and analyzed with the Wilcoxon signed rank test. The results of this study showed that there is an effect of jenga play therapy on decreased anxiety in preschool-aged children as seen from the results of wilcoxon's analysis signed rank test with a value of Z = -4,381 showed the significance of p value = 0.001 (p<0.05). There is an effect of jenga play therapy on decreased anxiety in preschool-aged children (4-6 years) due to hospitalization at Murni Teguh Memorial Hospital. Abstrak Hospitalisasi adalah suatu proses yang berencana atau darurat mengharuskan anak tinggal di rumah sakit, untuk menjalani terapi dan perawatan hingga pemulangannya kerumah. Hospitalisasi secara psikologis berdampak dalam beberapa hal yaitu depresi, stres, takut dan mengalami kecemasan. Salah satu intervensi yang dianjurkan adalah pemberian terapi bermain jenga. Penelitian ini bertujuan untuk mengetahui pengaruh terapi bermain jenga terhadap penurunan kecemasan pada anak usia prasekolah (4-6 tahun) akibat hospitalisasi di Murni Teguh Memorial Hospital. Jenis penelitian adalah quasy eksperimen dengan rancangan “One group pre test – Post test”. Total sampel dalam penelitian ini sebanyak 30 anak usia prasekolah dengan menggunakan teknik total sampling. Pengumpulan data dilakukan sebelum dan sesudah terapi bermain menggunakan instrumen Spance Children Anxiety Scale (SCAS) dan dianalisis dengan uji Wilcoxon signed rank test. Hasil penelitian ini menunjukan bahwa adanya pengaruh terapi bermain jenga terhadap penurunan kecemasan pada anak usia prasekolah yang dilihat dari hasil analisa Wilcoxon signed rank test dengan nilai Z = -4,381 menunjukkan signifikansi p value =0.001 (p<0,05). Terdapat pengaruh pemberian terapi bermain jenga terhadap penurunan kecemasan pada anak usia prasekolah (4-6 tahun) akibat hospitalisasi di Murni Teguh Memorial Hospital.